2022
DOI: 10.1002/mnfr.202101073
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Ulcerative Colitis: An Exploratory Study of the Effects of Red Wine Consumption on Gut and Oral Microbiome in Active‐Phase Patients

Abstract: Scope: This paper explores the effects of moderate red wine consumption on the clinical status and symptomatology of patients with ulcerative colitis (UC), including the study of the oral and intestinal microbiome. Methods and results: A case control intervention study in UC patients is designed. Intervention patients (n = 5) consume red wine (250 mL day −1 ) for 4 weeks whereas control patients (n = 5) do not. Moderate wine consumption significantly (p < 0.05) improves some clinical parameters related to seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Conversely, the genera Clostridia UCG-014 and Enterorhabdus [ 26 , 43 ] were increased in these luteolin and xanthohumol cohorts ( Table 3 , Supplementary Figure S4 ). In particular, the genus Enterorhabdus belongs to the polyphenol-degrading family Eggerthellaceae (phylum Actinomycetota ), which is associated with health status and reported to potentiate the production of the previously mentioned bioactive phenolic metabolites [ 26 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the genera Clostridia UCG-014 and Enterorhabdus [ 26 , 43 ] were increased in these luteolin and xanthohumol cohorts ( Table 3 , Supplementary Figure S4 ). In particular, the genus Enterorhabdus belongs to the polyphenol-degrading family Eggerthellaceae (phylum Actinomycetota ), which is associated with health status and reported to potentiate the production of the previously mentioned bioactive phenolic metabolites [ 26 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these outcomes led to an improvement in the quality of life of the participants of this exploratory study as revealed by the IBDQ-32 questionnaire. Although studies with a greater sample size are required, the integrated vision provided in this study has allowed us to establish the most complete scientific evidences to date on the impact of moderate wine consumption in IBD patients, as well as on the oral and intestinal microbiome and its physiological relevance [2,15].…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol content in the wine was 13.5% and the total phenolic content reached 2500 mg of gallic acid equivalents/L as determined by the Folin-Ciocalteau method. The polyphenol profile of the wine was analysed by UPLC-ESI-MS/MS [2].…”
Section: Winementioning
confidence: 99%
“…(39,40) The primary comparison of interest is between the combined intervention versus control. Assuming a mean change in the IBDQ-32 score of 16 ± 20 estimated from previous literature, (41)(42)(43)(44) αsignificance of 0⋅05 and power 95 %, a sample size of n 19 per arm is required with effect size of 0⋅8. To allow for ∼25 % drop-out, given the duration of this trial and based on previous literature, (45)(46)(47) n 25 participants will be recruited to each arm.…”
Section: Methodsmentioning
confidence: 99%